IMPACT OF ASEAN ECONOMIC INTEGRATION ON INVESTMENT IN THE ASEAN REGION - Bayu Prajanto (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2022)
Economic integration in ASEAN is a long process which until now has periodically shown significant progress. However, ASEAN's economic integration, especially in the field of economic growth, has been achieved by opening up local markets to regional markets through cooperation. This research is legally discussed. Analysis of the data used, namely empirical data will also be presented to complete the discussion. The results of the discussion show that countries in the ASEAN region are able to create a stable trade climate and are able to offer large potential benefits from trade carried out in ASEAN countries. With the economic integration, ASEAN countries are able to increase their competitiveness not only at the regional level, but also at the global level.